2023
DOI: 10.18535/ijsrm/v11i11.fa01
|View full text |Cite
|
Sign up to set email alerts
|

Fish Wastewater and Fish Scale: A Corn Soil Enhancer

Arnold Alegre,
Jessa Marie Alegre,
Guarin Maguate

Abstract: This study was conducted to determine the effects of fish waste water and fish scale as soil enhancer for the growth of sweet corn. The Experimental Research design with different treatments such as treatment 1 for 100% fish scale, treatment 2 for 100% fish waste water, treatment 3 for 50% fish scale and 50% fish water waste, and treatment 4 for commercialized fertilizer were employed for the growth of corn plants in terms of height, girth of stem, number of leaves and length of leaves. Mean and Post hoc analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On the other hand, the increase in the length of lateral roots reached 10.44% and 130.55% for both concentrations, respectively, compared to the control. This demonstrates the positive effect of using fish scales powder on enhancing the spread of the root system of corn seedlings, which may be attributed to improving the natural and chemical properties of the soil and increasing its content of organic matter (Sarkar, et al,2018;Alkhafaji, and Elkheralla, 2019;Alegre, et al, 2023) The data shown in Figure 4 shows the effect of using fish scales powder on the wet and dry weight of maize seedlings.…”
Section: Fig 3 Effect Of Using Fish Scales Powder On Root Length (Cm)...mentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, the increase in the length of lateral roots reached 10.44% and 130.55% for both concentrations, respectively, compared to the control. This demonstrates the positive effect of using fish scales powder on enhancing the spread of the root system of corn seedlings, which may be attributed to improving the natural and chemical properties of the soil and increasing its content of organic matter (Sarkar, et al,2018;Alkhafaji, and Elkheralla, 2019;Alegre, et al, 2023) The data shown in Figure 4 shows the effect of using fish scales powder on the wet and dry weight of maize seedlings.…”
Section: Fig 3 Effect Of Using Fish Scales Powder On Root Length (Cm)...mentioning
confidence: 86%
“…Implementing effective agricultural practices is crucial to achieving effective sustainability (Santana, et al, 2019), through reducing the expansion of the use of agricultural chemicals, especially mineral fertilizers, to replace them with organic fertilizers to preserve agricultural soil from deterioration and improve agricultural crop productivity, hence, preserving human health (Adam, et al, 2022). As these traditional crop production inputs are becoming depleting and harmful to our environment and ecosystem, it will threaten all life on Earth (Alegre, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%